Three-Tesla MRI does not improve the diagnosis of multiple sclerosis: A multicenter study. (17th July 2018) - Hagens, Marloes H.J.; Burggraaff, Jessica; Kilsdonk, Iris D.; de Vos, Marlieke L.; Cawley, Niamh; Sbardella, Emilia; Andelova, Michaela; Amann, Michael; Lieb, Johanna M.; Pantano, Patrizia; Lissenberg-Witte, Birgit I.; Killestein, Joep; et al.
Abstract : Objective: In the work-up of patients presenting with a clinically isolated syndrome (CIS), 3T MRI might offer a higher lesion detection than 1.5T, but it remains unclear whether this affects the fulfilment of the diagnostic criteria for multiple sclerosis (MS). Methods: We recruited 66 patients with CIS within 6 months from symptom onset and 26 healthy controls in 6 MS centers. All participants underwent 1.5T and 3T brain and spinal cord MRI at baseline according to local optimized protocols and the MAGNIMS guidelines. Patients who had not converted to MS during follow-up received repeat brain MRI at 3–6 months and 12–15 months. The number of lesions per anatomical region was scored by 3 raters in consensus. Criteria for dissemination in space (DIS) and dissemination in time (DIT) were determined according to the 2017 revisions of the McDonald criteria. Results: Three-Tesla MRI detected 15% more T2 brain lesions compared to 1.5T ( p < 0.001), which was driven by an increase in baseline detection of periventricular (12%, p = 0.015), (juxta)cortical (21%, p = 0.005), and deep white matter lesions (21%, p < 0.001). The detection rate of spinal cord lesions and gadolinium-enhancing lesions did not differ between field strengths. Three-Tesla MRI did not lead to a higher number of patients fulfilling the criteria for DIS or DIT, or subsequent diagnosis of MS, at any of the 3 time points. Conclusion: Scanning at 3T does not influence the diagnosis of MS according to McDonald diagnostic criteria.